Quantitative Analysis of Total Free Amino Acids in Some Wild Edible Plants of Kangchup Chingkhong, Manipur, North East India - Singh, O. N.; Kikim, A.; Niranjan, Ch. (International Journal of Economic Plants, 2026)
The present study, conducted from March to December, 2024, investigated the total free amino acid content in various parts of selected wild edible plant (WEP) species collected from Kangchup Chingkhong, Senapati District, Manipur, India, aimed to quantitatively estimate the total free amino acid content in various plant parts of selected wild edible species. WEPs are important sources of nutrition and health-promoting compounds for indigenous and rural communities, especially in Northeast India, where they contributed significantly to traditional diets and local food security. A total of 23 species representing different growth forms-trees, shrubs, herbs, and creepers-were analyzed using standard biochemical techniques. Plant parts such as leaves, stems, roots, flowers, rhizomes, fruits, seeds, bark, and tubers were examined to capture inter- and intraspecific variations in amino acid content. The total amino acid concentration varied widely among species and plant parts, reflecting differences in metabolic activity. Among trees, Parkia timoriana seeds showed the highest amino acid content (16.13±0.77 mg g-1), while Albizia myriophylla bark recorded the lowest (2.21±0.62 mg g-1). In shrubs, Acacia pennata stem recorded the maximum (16.76±0.60 mg g-1) amino acid content, and minimum (1.50±0.06 mg g-1) in Clerodendrum serratum flowers. Among herbs, Alpinia galanga rhizome contained the highest (18.98±0.71 mg g-1) amino acid content, while Curcuma amada rhizome had the lowest (1.28±0.17 mg g-1). In creepers, Paederia foetida leaves had the highest (2.14±0.23 mg g-1) amino acid content and its stem the lowest (1.39±0.06 mg g-1). The study highlighted the nutritional significance of these underutilised wild plants and their potential for inclusion in community nutrition programs, functional food development, and sustainable agricultural systems.